Assessing the Merits of the Clinton Health Care Reform Proposal - Kessler, Warren (Maine Policy Review, 1993)
The twentieth anniversary of the Governor’s Economic Development Conference last October focused on the impact of public policy on the competitiveness of Maine’s business and industry. Warren C. Kessler, president of Kennebec Health Systems, assesses the Clinton administration’s health care reform proposal.